Additive manufacturing applications in Defence Support Services: current practices and framework for implementation - Busachi, Alessandro; Erkoyuncu, John Ahmet; Colegrove, Paul A.; Drake, R.; Watts, C.; Wilding, Stephen (Springer, 2017)
This research investigates through a systems approach, “Additive Manufacturing” (AM) applications in “Defence Support Services” (DS2). AM technology is gaining increasing interest by DS2 providers, given its ability of rapid, delocalised and flexible manufacturing. From a literature review and interviews with industrial and academic experts, it is apparent that there is a lack of research on AM applications in DS2. This paper’s contribution is represented by the following which has been validated extensively by industrial and academic experts: (1) DS2 current practices conceptual models, (2) a framework for AM implementation and (3) preliminary results of a next generation DS2 based on AM. To carry out the research, a Soft System Methodology was adopted. Results from the research increased the confidence of the disruptive potential of AM within the DS2 context. The main benefits outlined are (1) an increased support to the availability given a reduced response time, (2) reduced supply chain complexity given only supplies of raw materials such as powder and wire, (3) reduced platform inventory levels, providing more space and (4) reduced delivery time of the component as the AM can be located near to the point of use. Nevertheless, more research has to be carried out to quantify the benefits outlined. This requirement provides the basis for the future research work which consists in developing a software tool (based on the framework) for experimentation purpose which is able to dynamically simulate different scenarios and outline data on availability, cost and time of service delivered.
Keywords: Additive manufacturing; Defence Support Service systems; Systems science